PENINGKATAN KREATIVITAS MATEMATIKA SISWA KELAS X KECANTIKAN 2 SMK NEGERI 10 MEDAN MELALUI PEMBELAJARAN PROJECT BASED LEARNING - Tiofanny Tiofanny (KOLONI, 2022)
This type of research is classroom action research (PTK) which aims to find out what efforts can be made to increase student creativity by applying the Project Based Learning (PjBL) model in class X Beauty 2 and to find out students' mathematical creativity after being taught using the Project Based Learning model ( PjBL) in class X Beauty 2 of SMK Negeri 10 Medan for the 2022/2023 Academic Year. The subjects of this study were 32 class X students of SMK Negeri 10 Medan in the Academic Year 2022/20233 and the objects in this study were students' mathematical abilities in material comparison with the PjBL model. From the research results obtained (1) efforts were made to increase mathematical creativity by applying the PjBL model in cycle I, namely asking students to review material comparisons and make conclusions in the words themselves; asking students to read the questions while underlining the important points; asking students to be active in groups and dare to give responses; and ask students to reassess the calculations made so that their conclusions are correct. The efforts made in cycle II were to form new groups based on students' abilities and ask students who had high abilities to teach their friends who did not understand; and apply the PjBL model by asking students to present the results of their group work and other friends provide feedback. (2) After being taught with the PjBL model, there was an increase in students' mathematical creative abilities. This can be seen from the student's initial ability test to the student's creativity test from cycle I to cycle II. In the initial ability test 8 students (14%) achieved the target of success. In the first cycle, the student success rate was 21 students (40.63%), and in the second cycle, the student success rate increased to 29 students (90.63%). Keywords: Project Based Learning, Mathematical Creativity, Classroom Action Research